Association of dietary habits and nutritional status with socioeconomic status of older adults attending a Municipal Program - Sánchez Ruiz, Fiorella (2014)
Background: The population of older adults has been increasing in the country. Addressing their problems is complex. They are considered a risk group, with health and nutrition problems related to socioeconomic and other factors. Objectives: To determine the association of dietary habits and nutritional status with socioeconomic status (SES) in older adults attending a Municipal Program. Design: Descriptive, cross-sectional association study. Setting: Municipal Program for Older Adults of 4 districts in Metropolitan Lima, Peru. Participants: Adults over 60 years of both sexes. Interventions: Weight and height were determined, and previously validated surveys on dietary habits and socioeconomic status were applied to 115 subjects who constantly attended a Municipal Program. Main outcome measures: Nutritional status according to body mass index, adequacy of eating habits according to recommendations, and socioeconomic status by Graffar's scale. Results: Overweight and obesity prevalence were respectively 42.6% and 19.1%. Over 60% had inadequate dietary habits regarding meat (65.2%), dairy (78.3%), beans (87.8%), fruits and vegetables (64.3%). Older adults were located mainly on the medium-low SES (37%) and medium-medium SES (33%). Nutritional status was not significantly associated with SES (p = 0.629). Dietary habits were significantly associated (P <0.05) with SES in the consumption of meat (p=0003), cereals and tubers (p=0038), and fruits and vegetables (p=0001). Conclusions: An association of food habits with SES but not with nutritional status was found in our study subjects.